2024
DOI: 10.3389/fimmu.2024.1359534
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Tlr5 deficiency exacerbates lupus-like disease in the MRL/lpr mouse model

Razan M. Alajoleen,
David N. Oakland,
Rana Estaleen
et al.

Abstract: IntroductionLeaky gut has been linked to autoimmune disorders including lupus. We previously reported upregulation of anti-flagellin antibodies in the blood of lupus patients and lupus-prone mice, which led to our hypothesis that a leaky gut drives lupus through bacterial flagellin-mediated activation of toll-like receptor 5 (TLR5).MethodsWe created MRL/lpr mice with global Tlr5 deletion through CRISPR/Cas9 and investigated lupus-like disease in these mice.ResultContrary to our hypothesis that the deletion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…TLR5 recognizes bacterial flagellin. A recent study by Alajoleen et al (2024) using TLR5-deficient MRL/lpr mice demonstrated a worsening of the disease, possibly due to an increased germinal center reaction and suppression of regulatory lymphocytes [100]. There have been very few studies on the role of TLR5 in SLE and LN.…”
Section: Tlr Signaling In Sle-an Update On Recent Findingsmentioning
confidence: 99%
“…TLR5 recognizes bacterial flagellin. A recent study by Alajoleen et al (2024) using TLR5-deficient MRL/lpr mice demonstrated a worsening of the disease, possibly due to an increased germinal center reaction and suppression of regulatory lymphocytes [100]. There have been very few studies on the role of TLR5 in SLE and LN.…”
Section: Tlr Signaling In Sle-an Update On Recent Findingsmentioning
confidence: 99%